Healthcare-associated infections in the postoperative period after cardiac surgery - Andrioli, Edivete Regina; Cavalheiro, Rubens Andrioli; Furtado, Guilherme Campos; Gomes, Walter José; Medeiros, Eduardo Alexandrino (International Journal of Infection Control, 2018)
Background: This study aimed to determine the incidence of healthcare-associated infections (HAIs) in patients undergoing cardiac surgery, analyzing data and clinical outcomes in patients with and without HAIs. Methods: This was a prospective cohort study involving 293 consecutive adult patients undergoing cardiac surgery between April 2011 and October 2012. Results: Of the 293 patients, 60 (24.9%) developed 73 HAIs: 24 surgical site infections, 24 pneumonias, 14 urinary tract infections (UTIs), and 11 bloodstream infections (BSIs). The incidence of ventilator-associated pneumonia was 14.6 cases/1,000 ventilator-days, whereas that of catheter-associated UTI was 7.15 cases/1,000 catheter-days and that of central line-associated BSI was 4.52 cases/1,000 central line-days. Of the 60 patients with HAIs, 20 (33%) died before postoperative day 90, compared with 18 (7.7%) of the 233 patients without HAIs (P < .001). Independent variables associated with infection were length of hospital stay (OR, 1.04; 95% CI, 1.01-1.06; P = .002), duration of urinary catheter use (OR, 1.19; 95% CI, 1.07-1.13; P = .001), and duration of central line use (OR, 1.07; 95% CI, 1.01-1.13; P = .032). Independent variables associated with mortality were Acute Physiology and Chronic Health Evaluation II score (OR, 1.27; 95% CI 1.14-1.42; P < .001), pneumonia (OR, 11.94; 95% CI, 3.83-37.17; P < .001), UTI (OR, 8.59; 95% CI, 1.91-38.7; P = .005), and BSI (OR, 6.16; 95% CI, 1.08-34.98; P = .040). Conclusion: Among the most important complications after cardiac surgery are HAIs. Patients who experience postoperative infections have increased length of hospital stay and mortality.